2016
DOI: 10.5603/kp.a2015.0115
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure is the strongest predictor of acute kidney injury in patients undergoing primary percutaneous coronary intervention for ST-elevation myocardial infarction

Abstract: A b s t r a c tBackground: ST elevation myocardial infarction (STEMI) patients treated by primary percutaneous coronary intervention (PCI) are at higher risk of acute kidney injury (AKI) than patients undergoing PCI in stable clinical conditions. This fact suggests that mechanisms other than contrast nephrotoxicity are involved. Aim:To evaluate the incidence, risk factors, and consequences of AKI in patients undergoing primary PCI for STEMI in current daily practice. Methods:Analysis of all consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
2
9
0
1
Order By: Relevance
“…In addition, low cardiac output, tubuloglomerular feedback, increased intra-abdominal pressure or increased venous pressure may result in kidney congestion [24]. Similar to our results, other studies on STEMI patients undergoing PPCI showed that AHF was an independent predictor of AKI [2,8,11,12,21,25,26].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, low cardiac output, tubuloglomerular feedback, increased intra-abdominal pressure or increased venous pressure may result in kidney congestion [24]. Similar to our results, other studies on STEMI patients undergoing PPCI showed that AHF was an independent predictor of AKI [2,8,11,12,21,25,26].…”
Section: Discussionsupporting
confidence: 87%
“…Variables identified as significant and independent predictors of AKI were peak NT-proBNP ≥400 pmol/L, which is indicative of AHF, as well as HAI and resuscitation before admission. In previous studies, the incidence of AKI in STEMI or acute coronary syndrome (ACS) patients, based on the AKIN or KDIGO criteria, ranged between 10% and18% [3,11,12,[19][20][21]. Moreover, Shacham et al reported that the AKI incidence was 6.2% in STEMI patients with preserved EF before PPCI [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Согласно данным J. Matějka и соавт., леталь ность у пациентов с ИМпST и КИОПП достигала 24 %, в то время как у пациентов без КИОПП -3,4 % (p=0,001) [28]. Эти данные согласуются с полученными нами результатами -летальность у пациентов с КИОПП и без КИОПП составила 14,5 и 6,1 % соответственно (p=0,037).…”
Section: Discussionunclassified
“…Renal failure proved to be strongly associated with a higher risk of death following PCI in acute cases, in a significantly higher extent than in stable coronary artery disease. A recent study demonstrated a double relative risk associated with renal failure in STEMI cases (odds ratio 5.3) as compared with ACS cases (odds ratio 2.1), and with stable coronary artery disease (odds ratio 2.3) [3].…”
mentioning
confidence: 99%